2012
DOI: 10.1136/heartjnl-2012-302230
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intracoronary cell therapy on left ventricular function in the setting of acute myocardial infarction: a meta-analysis of randomised controlled clinical trials

Abstract: Intracoronary BMC treatment leads to a moderate improvement of LVEF and reduction of LVESV at 6 months that sustained at 12 months follow-up, without a clear significant effect on LVEDV, or infarct size. Furthermore, we found that intracoronary cell therapy is significantly associated with a reduction in recurrent AMI and readmission for heart failure, unstable angina or chest pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 41 publications
1
46
1
Order By: Relevance
“…Combining bioactive materials with stem cell products represents a natural extension of these approaches given recent meta-analyses demonstrating only modest persistence of injected stem cell products alone (approx. 1-2%) beyond 12 months [5,12,25,26]. As such, a variety of biomaterials have entered active development with the intent of providing a supportive scaffold that improves both acute cell retention and long-term cell viability [8,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…Combining bioactive materials with stem cell products represents a natural extension of these approaches given recent meta-analyses demonstrating only modest persistence of injected stem cell products alone (approx. 1-2%) beyond 12 months [5,12,25,26]. As such, a variety of biomaterials have entered active development with the intent of providing a supportive scaffold that improves both acute cell retention and long-term cell viability [8,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…There has been controversy over the possible efficacy and mechanism of BM treatment of MI focused around the persistence and function of stem cells in the myocardium [7,8,35], with findings both dismissing and supporting the trans-differentiation of non-cardiac lineage stem cells into functional cardiomyocytes and endothelial tissue. Despite these contradictions, there is a growing body of data from studies of bone marrow derived cell transplantation post-MI in animal models [9,[36][37][38] and human clinical trials [2,14,23,[39][40][41][42] that show improvements in heart function over the short and long term consistent enough to be retained in extensive meta-analysis [24]. The variability in reported data highlight the need to better understand what makes some cellular therapies successful whilst others effect no improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Autologous CD34 + cells infused into the infarcted artery of acute MI patients in human trials showed a similar positive response to the findings in rat models [23], although this was not carried out in direct comparison to the total BM cell population. A 2012 meta-analysis of randomized controlled clinical trials concluded intracoronary delivery of BM cells significantly increased functionality and reduced MI reoccurrence [24]. Comparisons of the relative efficacies of different cells types have shown BM mononuclear cells to be more effective than BM mesenchymal stem cells (MSC) [25] and adult HSC to be more effective than cord blood stem cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…27-29 a recent meta-analysis by delewi et al 30 revealed that intracoronary BMC treatment leads to a moderate improvement in lveF and a reduction of left ventricular end-systolic volume (lvesv) at 6 months that sustained at 12 months follow-up, without a clear significant effect on left ventricular end-diastolic volume (lvedv) or infarct size. the authors also found that intracoronary cell therapy was significantly associated with reductions in recurrent acute Mi and readmission for hF, unstable angina, or chest pain.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 99%